2013
DOI: 10.1186/1471-2164-14-696
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146 function in the innate immune transcriptome response of zebrafish embryos to Salmonella typhimurium infection

Abstract: BackgroundMicroRNAs (miRNAs) have recently been shown to play important roles in development of the immune system and in fine-tuning of immune responses. Human miR-146 family members are known as inflammation-inducible miRNAs involved in negative feedback regulation of Toll-like receptor (TLR) signalling. Dysregulation of the miR-146 family has often been linked to inflammatory diseases and malignancies. This study reports on miR-146a and miR-146b as infection-inducible miRNAs in zebrafish, which has emerged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 62 publications
2
50
0
Order By: Relevance
“…Initiation of the MyD88-independent pathway leads to the activation of IFN-regulatory factor 3 (IRF3) and the expression of INF-b and IFN-inducible genes. 14 In zebrafish models, research also shows that TLR signaling pathways play a central role in immune response during infection and inflammation. [15][16][17] It is reasonable to speculate that TLR signaling pathway sensing of gut bacteria and provoking inflammatory response is essential in IBD pathogenesis, but it remains to be directly proved how changes in the commensal composition functionally slant TLR signaling in the disease.…”
mentioning
confidence: 99%
“…Initiation of the MyD88-independent pathway leads to the activation of IFN-regulatory factor 3 (IRF3) and the expression of INF-b and IFN-inducible genes. 14 In zebrafish models, research also shows that TLR signaling pathways play a central role in immune response during infection and inflammation. [15][16][17] It is reasonable to speculate that TLR signaling pathway sensing of gut bacteria and provoking inflammatory response is essential in IBD pathogenesis, but it remains to be directly proved how changes in the commensal composition functionally slant TLR signaling in the disease.…”
mentioning
confidence: 99%
“…This gene was found to be highly expressed in vascular smooth muscles [19], endothelial cells [20], cardiomyocytes [21] and cardiac fibroblasts [22]. Another miR, miR-146a, was shown to be a negative feedback regulator of inflammatory responses [10] and to be involved in regulating innate immune responses [23,24]. Recently, miR-146a expression in myocardial tissue was reported to increase with the onset of MI [24].…”
Section: Introductionmentioning
confidence: 99%
“…5A). Mammalian miR-146 family members (miR-146a and miR-146b) are inflammation-inducible miRNAs involved in negative feedback regulation of the TLR signaling pathway (39), which are also induced by bacterial infection in zebrafish in a MyD88-and TRAF6-dependent manner (40). The qRT-PCR assay revealed that miR-146a and miR-146b were also significantly upregulated after bacterial infection (Fig.…”
Section: Tandem 39 Utr Switching After Bacterial Challengementioning
confidence: 98%